(untitled) (Physical Education, Health and Social Sciences, 2025)
The Accumulation levels of heavy metals for intestine, muscle, gill and liver tissues of two freshwater fishes Shizothorax Plagiostomus and Crossocheilus Diplocheilus were investigated. The heavy metals such as Cobalt, Zinc, Nickel and Cadmium were determined through atomic absorption spectrophotometer. The aim of current study to evaluate heavy metal concentration in different organs of two freshwater fishes. The concentration of heavy metals is lowest in gills of both species. Metals accumulated in the body of Schizothorax Plagiostomus in order of Cd >Zn >Ni >Co. Metals concentration in various organs of Schizothorax Plagiostomus was intestine> liver> muscle> gills. Whereas, the concentration of heavy metals in different organs of Crossocheilus Diplocheilus was intestine> muscles> liver and gills. Similarly, the accumulation pattern of heavy metals in the body of Crossocheilus Diplocheilus was Cd> NI> Zn> Co. The accumulation pattern of heavy metals was different in both species, while in both species Cd was highest and Co was less accumulated heavy metal. The current study has reported that the concentration of heavy metals Zn, Ni, Cd and Co are more in Schizothorax Plagiostomus as compared to Crossocheilus Diplocheilus.